Boko Haram Insurgency and the 2015 General Elections in Nigeria (Journal of International Studies, 2015)
This is a study of the Boko Haram insurgency in Nigeria, and how it affected the 2015 General Elections in the country. The Boko Haram is a Muslim fundamentalist sect founded in 2002, but the insurgency it mounted in Nigeria in 2009 has dovetailed into politics. By the time of the 2015 elections in Nigeria, the insurgency had become the foremost political issue in the country. Boko Haram was central in the campaigns for the elections, and the fortunes of the political parties and their candidates literally depended on where they stood concerning the Boko Haram matter. Interestingly, the elections also affected the fortunes of Boko Haram as the incumbent government at the time had to come out in full force against the sect as a way of shoring up its chances at the polls. Since after the polls, the viability of the insurgency has considerably reduced, although the sect continues to pose a threat to the country. This paper argues that beyond victory in the battlefi eld, the government of Nigeria must also improve on its governance practices in order to remove the socio-economic conditions that help to sustain Boko Haram and other such militant groups in Nigeria.